TINJAUAN HUKUM OBAT TRADISIONAL BERBAHAN KIMIA OBAT - Putri, Ruri Eka; Zamroni, Mohammad; Huda, Mokhamad Khoirul (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2021)
AbstractThis study aims to determine the rights and obligations of makers and distributors of traditional medicines and analyze the legal responsibilities of makers and distributors of traditional medicines that contain chemical drugs. The research method in this paper is normative or doctrinal research using a law approach, conceptual approach, and case approach. The research materials combined any legal material such as primary, secondary, and tertiary. The technique of processing legal materials is to inventory, identify, classify and systematize according to the hierarchy of the legislative order, and analyzed. The nature of this research is analytical descriptive. The results show that the rights and obligations as well as the forms of legal responsibility for the makers and distributors of traditional medicines, which are regulated in various laws that are still general in nature. The threat of sanctions for violations of traditional medicines containing medicinal chemicals can be criminal, civil, and administrative. It is hoped that there will be separate or special rules and laws governing the rights, obligations, and responsibilities for the makers and distributors of traditional medicines that contain chemical drugs.Keywords: chemical drugs; legal liability; traditional medicineAbstrakPenelitian ini bertujuan untuk menganalisis hak dan kewajiban pembuat maupun pengedar obat tradisional serta tanggung jawab hukum pembuat dan pengedar obat tradisional yang mengandung bahan kimia obat. Metode yang digunakan adalah yuridis normatif atau doktrinal menggunakan pendekatan hukum, pendekatan konseptual, serta pendekatan kasus. Bahan penelitian meliputi bahan hukum mulai dari primer, sekunder dan hingga tersier yang diolah menggunakan teknik pengolahan melalui inventarisasi, identifikasi, klasifikasi, kemudian disistemisasi sesuai urutan perundang-undangan melalui deskriptif analisis. Hasil penelitian menunjukkan bahwa hak dan kewajiban serta bentuk tanggung jawab hukum untuk pembuat dan pengedar obat-obatan tradisional diatur dalam berbagai peraturan dan undang-undang yang masih bersifat umum. Ancaman sanksi bagi pelanggaran obat-obatan tradisional yang mengandung bahan kimia obat-obatan dapat berupa pidana, perdata, hingga administratif sebagaimana yang tertuang dalam berbagai sumber hukum yang telah dianalisis. Diharapkan perlu adanya aturan dan undang-undang tersendiri yang mengatur hak, kewajiban serta pertanggungjawaban pembuat dan pengedar obat tradisional berbahan kimia obat.